Mathematical Game Theory in Optimal Strategy Analysis for E-Wallet Competition (Case Study: Users of GoPay, DANA, and OVO in Makassar City) - Irwan; Side, Syafruddin; Khadijah , Ummul (Jurusan Matematika FMIPA UNM, 2025)
. Game theory is a branch of applied mathematics within operations research that focuses on studying and understanding competitive situations involving multiple parties. The rapid growth of e-wallet usage has significantly intensified competition in the digital sector. This study aims to analyze the optimal strategies in the e-wallet competition between GoPay, DANA, and OVO in Makassar City using game theory. The data utilized in this research were obtained through a questionnaire survey involving 100 student respondents. Six strategic attributes are examined: product, price, promotion, place, practicality, and security. The results indicate that in the competition between GoPay and OVO, GoPay's optimal strategy is to focus on promotion to maximize profits, while OVO's optimal strategy is prioritizing security to minimize losses. In the competition between DANA and OVO, DANA's optimal strategies include product, price, and place to achieve maximum profits, while OVO focuses on product, promotion, and place to minimize losses. Meanwhile, in the competition between DANA and GoPay, DANA's optimal strategies are price, practicality, and security to maximize profitability, while GoPay prioritizes price, place, and security to minimize losses. These findings demonstrate the varying strategic approaches each e-wallet employs to adapt to the competitive market dynamics and optimize outcomes based on their respective priorities and strengths